Open access publishing trend analysis: statistics beyond the perception - Poltronieri, Elisabetta; Bravo, Elena; Curti, Moreno; Ferri, Maurizio; Mancini, Cristina (Information research, 2016)
Introduction. The purpose of this analysis was twofold: to track the number of open access journals acquiring impact factor, and to investigate the distribution of subject categories pertaining to these journals. As a case study, journals in which the researchers of the National Institute of Health (Istituto Superiore di Sanita) in Italy have published were surveyed. Method. Data were collected by searching open access journals listed in the Directory of Open Access Journals ) then compared with those having an impact factor as tracked by the Journal Citation Reports for the years 2010-2012. Journal Citation Reports subject categories were matched with Medical Subject Headings to provide a larger content classification. Analysis. A survey was performed to determine the Directory journals matching the Journal Citation Reports list, and their inclusion in a given subject area. Results. In the years 2010-2012, an increase in the number of journals was observed for Journal Citation Reports (+ 4.93%) and for the Directory (+18.51%). The discipline showing the highest increment was medicine (315 occurrences, 26%). Conclusions. From 2010 to 2012, the number of open access journals with impact factor has gradually risen, with a prevalence for journals relating to medicine and biological science disciplines, suggesting that authors prefer to publish more than before in open access journals.